Suggestions for the Development of Telemedicine in Mongolia: Reviewing Development History of Telemedicine in the Republic Of Korea (Central Asian Journal of Medical Sciences, 2016)
Objectives: This study reviews the history of telemedicine in Korea and presents future directions for telemedicine. Methods: Journal papers, reports, and government publications on telemedicine were collected and reviewed as technological advances sequenced in chronological order. Results: Development of telemedicine in the Republic of Korea was promoted by revising medical law in 2003 and introducing broadband internet services in 1999. Conclusion: For the success of the introduction of telemedicine, financial support has become the key to ensuring stable operations. Telemedicine services must be suitably priced, which calls for revisions to related legal and administrative policies.